A new olanzapine cocrystal obtained from volatile deep eutectic solvents and determined by 3D electron diffraction. Issue 6 (7th December 2020) - Andrusenko, Iryna; Potticary, Jason; Hall, Simon R.; Gemmi, Mauro
Abstract : A new olanzapine–phenol cocrystal was discovered as an intermediate product during the crystallization of olanzapine from volatile deep eutectic solvents. The ability of 3D ED to investigate nanocrystalline intermediate forms paves the way for a thorough understanding of the crystallization pathways in pharmaceutical chemistry. Abstract : A previously unknown cocrystal of olanzapine and phenol was identified from a volatile deep eutectic solvent as the intermediate species in the crystallization of olanzapine. This new nanocrystalline phase was investigated by electron diffraction, powder X‐ray diffraction and differential scanning calorimetry. The structure was determined by simulated annealing using 3D electron diffraction data and confirmed using DFT‐D optimizations. Olanzapine and phenol cocrystallize in the triclinic space group P 1, supporting the hypothesis of a dimeric growth unit, where a centrosymmetric dimer is stabilized by multiple weak C—H…π interactions and forms double N—H…N hydrogen bonding with adjacent dimers.